UNVEILING THE ROLE OF PARENTAL INVOLVEMENT IN ENHANCING ELEMENTARY SCHOOL STUDENTS' LEARNING OUTCOMES - Andriana, Encep; Rokmanah, Siti; Ramadhani, Chairunnisa Oktorina (PROGRES PENDIDIKAN, 2025)
This study aims to examine the impact of parental involvement on students' learning outcomes, the key factors supporting parental involvement, and the challenges faced by parents. This article employs a Systematic Literature Review (SLR) approach. A total of 25 relevant articles were selected after undergoing a screening process based on inclusion and exclusion criteria. The research process includes gathering information, filtering relevant data, and analyzing the findings. The results indicate that parental involvement plays a crucial role. Supporting factors include the availability of quality time between parents and students, motivation and support provided to students, collaboration between parents and teachers, parents' educational background, family economic status, and the utilization of technology. The implications of these findings highlight the importance of fostering stronger parent-teacher partnerships to enhance student outcomes. Schools should consider implementing programs that educate parents on effective ways to support their children’s learning at home. Additionally, policymakers could prioritize providing resources and support systems for families from diverse socioeconomic backgrounds, enabling equitable access to tools and opportunities that facilitate parental involvement.